Socio-Economics and Economic Sociology: the Points of Differences and Integration - ШабановаМарина Андриановна (Journal of Economic Sociology, 2010)
The author tries to demonstrate the differences and points for integration of socio-economics and economic sociology. This is the first detailed review on this issue that was done in Russian language.